2016
DOI: 10.21608/bvmj.2016.31282
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin residues in chicken and turkey carcasses

Abstract: Ciprofloxacin residues were detected in chicken and turkey tissues "thigh, breast, liver and kidney" by using HPLC. Results reflected a significant difference variation among kidney, liver, breast and thigh in examined chicken and turkey samples as p values <0.05 indicating that kidney and liver are the site of accumulation of ciprofloxacin residues The highest residual level of ciprofloxacin found in kidney then liver Whereas the lowest concentrations were found in breast then thigh muscles. The means average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Hasanen et al [129] studied ciprofloxacin residues in chicken and turkey carcasses. They concluded that ciprofloxacin residues are heat-stable and are not degraded by any cooking method, except microwaves (800 W) for 15-20 min in muscles and 3-5 min in the liver and kidney, also freezing for one month at −20 • C can degrade ciprofloxacin and its metabolites to levels below the permitted limits, but not below detectable levels.…”
Section: Effect Of Food Processing On the Residues Of Antibiotics Fou...mentioning
confidence: 99%
“…Hasanen et al [129] studied ciprofloxacin residues in chicken and turkey carcasses. They concluded that ciprofloxacin residues are heat-stable and are not degraded by any cooking method, except microwaves (800 W) for 15-20 min in muscles and 3-5 min in the liver and kidney, also freezing for one month at −20 • C can degrade ciprofloxacin and its metabolites to levels below the permitted limits, but not below detectable levels.…”
Section: Effect Of Food Processing On the Residues Of Antibiotics Fou...mentioning
confidence: 99%
“…The heat treatment methods of boiling, grilling, and roasting do not affect the degradation of ciprofloxacin residues. As ciprofloxacin is a heat-stable compound that gets degrade less by the heat treatment process, microwaving and freezing will greatly reduce the ciprofloxacin residue (Hasanen et al, 2016 [15] ; Gogoi and Roy, 2019) [13] still freezing is the efficient method to degrade ciprofloxacin residues to a safe level than microwaving (Fahim, 2019 [8] ; Shaltout et al, 2019) [44] .…”
Section: Ciprofloxacinmentioning
confidence: 99%
“…Enrofloxacin is metabolized into ciprofloxacin in most species. However, as residues, both enrofloxacin and ciprofloxacin are heat-stable compounds (Hasanen et al 2016) and thus represent a serious health concern. Some countries (see Table 1) had established the maximum residue limit (MRL) of enrofloxacin, calculated as the sum of enrofloxacin and ciprofloxacin.…”
Section: Introductionmentioning
confidence: 99%